KONFLIK DAN HARMONISASI REGULASI HAK ATAS TANAH LAUT: STUDI LITERATUR TENTANG PENATAAN WILAYAH PESISIR DAN IMPLIKASINYA TERHADAP PENEGAKAN HUKUM DAN PERLINDUNGAN HAK MASYARAKAT - Gunawan Widjaja (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study discusses conflicts and harmonisation of regulations related to maritime land rights in the context of coastal zone management in Indonesia and their implications for law enforcement and the protection of community rights. Regulatory conflicts arise due to sectoral legal paradigms that give rise to overlapping norms between the Basic Agrarian Law, the Coastal Zone and Small Islands Management Law, the Maritime Law, the Environmental Law, and spatial planning regulations. This lack of synchronisation not only has an impact on weak legal certainty and the effectiveness of law enforcement, but also causes the marginalisation of coastal communities, particularly traditional fishermen and indigenous communities, whose rights are often neglected by investment-based and coastal industrialisation policies. This study uses a normative juridical method through a literature review approach by analysing primary, secondary, and tertiary legal materials, as well as exploring the theories of legal harmonisation and legal pluralism. The results show that regulatory conflicts create disharmony in coastal governance, which has an impact on ecological and social vulnerability in coastal areas. Therefore, regulatory harmonisation is necessary through the integration of sectoral laws, recognition of indigenous peoples' rights, public participation in the legislative process, strengthening coordination between institutions, and continuous evaluation of regulations. With proper legal harmonisation, it is hoped that coastal area governance can be realised in a fair and sustainable manner, upholding the principles of protecting community rights and the rule of law.